INTEGRASI PENGAJIAN SAINS-TEKNOLOGI DAN PENGAJIAN SYARIAH: SATU PENILAIAN SEMULA - Alias Azhar (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
The development of shari’ah is being questioned because it has deviated from the original purpose and tends to focus more on formal aspects than on its application and usefulness for life. Therefore, it is the time to re-evaluate the strategy and execution of all forms of shari’ah to fi t with the modern era and improve the business of ummah to cover the advancement of science and technology. There are two choices in establishing the patterns of shari’ah studies. First, follow the trends with tecnical, bureaucratic and legal also formal rule that will make Islamic shari’ah static. Secondly, formulate the paradigm of integrated shari’ah studies covering the development of science and technology whose purpose is to establish a dynamic and responsive Islamic law to the problems of society.